POLIPLOIDISASI TANAMAN JAHE MERAH (Zingiber officinale Var. Rubrum) MENGGUNAKAN MUTAGEN KOLKISIN - Fransiska Mandela; Reza Prakoso Dwi Julianto; Mohamad Nurul (Universitas Tribhuwana Tunggadewi, 2021)
This study aimed to obtain recommendations for effective treatment times to increase the growth and yield of ginger plants. The research used a Randomized Block Design, colchicine immersion time was used in this research as the treatments, including 0 hours (control) (L0), 4 hours (L1), 8 hours (L2), 12 hours (L3), and 16 hours (L4). The results showed that were differences in colchicine immersion time caused significant differences between diploid and polyploid plants. The morphological characters of plant height, rhizome weight, productivity, and essential oil, while the morphological characters of root length and rhizome diameter were soaked in colchicine for 8 and 12 hours showed a non-significant difference. Colchicine soaking for 12 hours is the most effective treatment to increase the growth and yield of red ginger plants and has an optimal essential oil content.